Pre-empting the future: training of a landscape architect - Zen, Ismawi (2011)
In order for landscape architecture to continue to be relevant in a world of insatiable demand on nature, which is oiled by seemingly unabated globalization, the single biggest challenge is to produce landscape architects who are holistic as well versatile. His training must be futuristic targeted to achieve man matrix of: i) Creativity: The ability to synthesize functional requirements, cultural peculiarities and the economics of matters within the framework of environmental-friendly approach to nature. ii) Knowledge: The ability to research, document and synthesize all aspects of landscape architecture. iii) Skill: The ability to communicate ideas and decisions.iv) Awareness: The realization every action will impact life patterns of the affected society. v) Adaptability: The ability to realize ideas using progressively complex knowledge and technology. Knowledge acquisition therefore entails hogging the upward spiral of the quality path: i) Knowledge delivery, ii) Knowledge discovery, iii) Knowledge construction and iv) Knowledge innovation and diffusion.